ANALYSIS OF THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND PRODUCT INNOVATION ON CONSUMER PURCHASING DECISIONS AT MARTUBUNG VAPE STORE - Try Rahayu; Nuzuliati; Cindy Yolanda; Fatmawati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The intense competition in the vape industry and the similarity of products between stores require businesses to understand the factors that influence consumer purchasing decisions. In this context, digital information through electronic word of mouth and the level of product innovation are important factors influencing consumer purchasing decisions at Martubung Vape Store. This study aims to determine the partial influence of electronic word of mouth on purchasing decisions, the partial influence of product innovation on purchasing decisions, and the simultaneous influence of electronic word of mouth and product innovation on consumer purchasing decisions at Martubung Vape Store. This study was conducted at Martubung Vape Store, with a total consumer population of 380 in 2024. The sampling technique used 5% of the total population, resulting in a sample size of 79 respondents. The results show that electronic word of mouth has a partial positive and significant effect on consumer purchasing decisions with a significance value of 0.000 < 0.05. Product innovation also has a partial positive and significant effect on consumer purchasing decisions with a significance value of 0.000 < 0.05. Simultaneously, electronic word of mouth and product innovation have a positive and significant effect on purchasing decisions, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.698 indicates that 69.8% of the variation in consumer purchasing decisions can be explained by electronic word of mouth and product innovation, while the remaining 30.2% is influenced by other factors outside this study.